Phase‐contrast MR flow imaging: A tool to determine hepatic hemodynamics in rats with a healthy, fibrotic, or cirrhotic liver. Issue 5 (27th February 2017) - Schaffner, Denise; von Elverfeldt, Dominik; Deibert, Peter; Lazaro, Adhara; Merfort, Irmgard; Lutz, Lisa; Neubauer, Jakob; Baumstark, Manfred W.; Kreisel, Wolfgang; Reichardt, Wilfried
Abstract : Purpose: To test a magnetic resonance (MR) scanning protocol as a noninvasive tool to determine hepatic hemodynamics and to assess the degree of liver fibrosis in an animal model of liver fibrosis and cirrhosis. Materials and Methods: Fifty‐four male Wistar rats were studied. Thirty‐nine received thioacetamide (TAA) in their drinking water for either 12 or 16 weeks. MR measurements were performed using flow‐sensitive 2D phase‐contrast MRI and a 9.4T preclinical scanner. The following hemodynamic parameters were investigated: portal cross‐sectional area, mean portal flow velocity, and portal and aortic flow volume rate. Therefore, rats ( n  = 46) were divided into three groups: CON (control, n  = 13), FIB (fibrosis, n  = 25), and CIR (cirrhosis, n  = 8). Furthermore, the degree of liver fibrosis was assessed by a self‐established MR score and verified by a standardized histological score ( n  = 48). Results: Portal and aortic flow parameters could be reliably detected. A significant decrease in portal flow velocity was found in FIB (FIB vs. CON: –21%, P  = 0.006 and CIR vs. CON: –17%, P  = 0.105) and in portal flow volume rate in FIB and CIR (FIB vs. CON: –20%, P  = 0.009 and CIR vs. CON: –25%, P  = 0.024). If the histological score is taken as standard, the self‐established MR score enabled discrimination between healthy and diseased livers (sensitivity to identify diseased livers: 89% and specificity to identify healthy livers: 100%). Conclusion: This MR scanning protocol presents a noninvasive tool to determine hepatic hemodynamics in healthy and diseased rats. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1526–1534.